Doing ethics - Vaughn, Lewis (W.W. Norton & Co., 2008)
Stressing critical thinking throughout the book, Lewis Vaughn motivates students to wrestle with moral quandaries from the start. His clear prose ensures that students understand major arguments and core concepts, and the extensive readings and exercises provide plenty of thought-provoking material for in-class discussions and student papers. Practical, clear and comprehensive, Doing Ethics will inspire students to see ethics not just as a distribution requirement, but as a lifelong project